Job Quality Improvement Training: Analysis of Notary Performance Improvement - Herlina Sakawati; Muhammad Fajri Syapar; Sulmiah; Widyawati (Technium Social Sciences Journal, 2023)
Notaries are public officials whose roles and obligations are necessary for society and the state. As a very necessary profession, a notary should have good performance, but several media broadcasts that in Indonesia notaries tend to abuse their authority and violate the notary’s code of ethics. The provision of training to improve the quality of positions is carried out by the government for prospective notaries to improve the performance of notaries. Through qualitative research, this study aims to find out how much influence the training has on notary performance improvement. Research data was obtained using a questionnaire and processed using SPSS. The findings of this study indicate that the effect of training on improving the quality of positions on notary performance improvement is 16.1%. From this training, notaries become disciplined at work, can carry out work effectively and efficiently, and work patterns are getting better by applying a careful pattern in completing work.